Bacterial diseases of tilapia, their zoonotic potential and risk of antimicrobial resistance - Haenen, Olga L. M.; Ha, Thanh Dong; Truong, Dinh Hoai; Crumlish, Margaret; Karunasagar, Iddya; Barkham, Timothy; Chen, Swaine L.; Zadoks, Ruth; Kiermeier, Andreas; Wang, Bing; Gamarro, Esther Garrido; Takeuchi, Masami; et al. (John Wiley & Sons Australia, 2023)
Tilapia culture is an important source of income and nutrition to many rural families. Since 2000, the production of tilapia increased and reached domestic and global markets. Major farmed species is Nile tilapia (Oreochromis niloticus), in earthen ponds and cage cultures. Intensification contributed to global tilapia disease outbreaks, with bacterial infections causing mortalities and morbidities, threatening sustainable production. At tilapia farms, high nutrient concentrations, water temperature and fish densities enhance bacterial growth including virulent bacterial clones and potential zoonotic bacteria. Global warming favours this. This review respectively provides a comprehensive overview of the most common and emerging bacterial pathogens, diseases, clinical presentations and diagnostics of tilapia, including bacteria and diseases with zoonotic potential. First, common bacterial disease outbreaks, including streptococcosis, motile Aeromonas septicaemia, francisellosis, columnaris disease and vibriosis are described. Then, information on emerging bacterial infections of concern for tilapia, like edwardsiellosis through Edwardsiella ictaluri and E. tarda, as well as Aeromonas schubertii is provided. Reports of infectious bacterial tilapia disease outbreaks from other bacteria, including Lactococcus garvieae, Aerococcus viridans, Pseudomonas spp., Mycobacterium marinum and Chlamydia spp., and others are reviewed. Furthermore, bacteria with zoonotic potential, like Streptococcus agalactiae ST283, S. iniae, Aeromonas sp., E. tarda, Vibrio vulnificus pathovar (pv) piscis and M. marinum are included in the review, to provide the most current overview of the disease risks affecting production and post-harvest stages. Additionally, the status and risks of antimicrobial resistance in bacteria from tilapia and other cultured fish through imprudent use of antibiotics, and its future at a global level are provided.